(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: COVID-19, a pandemic prevalent for a long time presents a multistep crisis;the first stage is an acute health crisis, followed by a healthcare recovery crisis in the second stage and a socio-economic crisis in an indefinite period. The study explores the challenges and specific concerns among patients diagnosed with cancer and their caregivers during the pandemic. Materials and Method: Qualitative research employs specific research methods such as in-depth interviews, content analysis, observation methods, and life histories or biographies to examine people’s experiences in detail. In the present study, a semi-structured questionnaire was developed and interviews were conductedto understand the experiences of cancer patients andtheir caregivers with health care and their daily challenges during the pandemic. A Non-random sampling method, involving males and females, within the age group of 18 to 65 years, and their primary care providers from the Regional Cancer Centre and other cancer hospitals are followed. Semistructured interview responses were collected from cancer patients and their caregivers., illustrative quotes were summarised and key themes from the interviews were extracted. Results and analysis: 9 Key themes with 20 subthemes were extracted in the content analysis. Difficulty having access to medical care, fear of infection transmission, lack of social support, loss of income source, drastic lifestyle changes, uncertainty about disease cure, and apprehension about the future,which result in cumulative disease burdenhave been frequently reported in the study. Conclusion: The current research is relevant in describing the experiences and perspectives of cancer patients and their caregivers, throwing light on the psychosocial issues and challenges during the pandemic situation, thus emphasizing the need for developing a supportive psychosocial intervention.